HUBUNGAN HIGIENE DAN SANITASI DENGAN KONTAMINASI ESCHERICHIA COLI PADA JAJANAN PEDAGANG KAKI LIMA DI SEKOLAH DASAR KELURAHAN PENDRIKAN LOR, SEMARANG - Azzahra Pratadina; Yusniar Hanani Darundiati; Hanan Lanang Dangiran (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Food, beverage and snack are the intake that have important role with human body for human growth and human development, especially to the children. There are so many street vendors in school ( especially elementary school) that supply many variaties snacks that have not already guaranteed their health, hygiene and sanitation. The purpose of this research is to know the relation between hygiene-sanitation practice and E. Coli contamination in food, beverage and snack of street vendors at elementary school. The variables that is examined in this study are hygiene practice of street vendors, sanitation practice of street vendors, the characteristic of food handler are include gender, age, education and years of service. This study use cross sectional method with 15 sample of street vendors, 19 snacks of street vendors at Elementary school in Pendrikan Lor Vilage, Semarang. Escerichia coli in food, beverage and snack as samples was measured by MPN methode ( Most Probable Number) with 9 times dilution. The results of this study are found 2 kinds of food and beverage, they are ice tea and meatball. All of street vendors have bad result in hygiene practice and in sanitation practice. From this research found that relation between sanitation practice with Eschericia coli contamination, the p value is 0,372. The conclusion of this research is there isn’t corelation between higiene practice with E. Coli contamination and there isn’t corelation between sanitation practice with E. Coli contamination. It is expected that street vendors selling around the elementary school especially Pendrikan Lor subdistrict follow the socialization class of good hygiene and sanitation practices and apply them when they are selling. It is expected that the school provides education to his students to choose good and healthy snacks only for consumption and not snack carelessly.